Key factors for successful cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy to treat diffuse malignant peritoneal mesothelioma: results from specialized peritoneal cancer center in China. (31st December 2022) - Su, Yan-Dong; Yang, Zhi-Ran; Li, Xin-Bao; Yu, Yang; Du, Xue-Mei; Li, Yan
Abstract: Objectives: To investigate independent factors for the efficacy and safety of cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) for the treatment of diffuse malignant peritoneal mesothelioma (DMPM). Methods: The clinical database of 110 DMPM patients treated with CRS + HIPEC at our hospital was retrospectively analyzed. Independent prognostic factors were screened using univariate and multivariate analyses and the safety of the perioperative period was evaluated based on adverse events. Results: Among the 110 patients with DMPM, 34 (30.9%) had a peritoneal cancer index (PCI) < 20 and 76 (69.1%) had PCI ≥20; 59 (53.6%) patients achieved completeness of cytoreduction (CC) 0/1 and 51 (46.4%) cases achieved CC 2/3. At the median follow-up of 43.3 (95%CI: 37.3–49.4) months, 48 (43.6%) patients were still alive and 62 (56.4%) patients died. The median overall survival was 32.6 months. Serious adverse events (SAEs) occurred in 41 patients (37.3%) and the perioperative mortality rate was 2.7%. Univariate analysis identified nine prognostic factors: Karnofsky performance status score, perioperative tumor markers, PCI, red blood cell infusion, pathological type, vascular tumor emboli, lymphatic metastasis, Ki-67 index, and perioperative SAEs (all p < 0.05). Multivariate analysis identified four independent prognostic factors: pathological type ( p = 0.007), vascular tumor emboli ( p = 0.044), Ki-67 index ( p = 0.044), and SAEs ( p = 0.004). Conclusions: CRS + HIPEC for DMPM treatment resulted in prolonged survival with acceptable safety. Tumor pathology and SAEs are key factors for successful CRS + HIPEC.